March - Lewis, John 1940-2020; Aydin, Andrew (Top Shelf Productions, 2016)
March is a vivid first-hand account of John Lewis' lifelong struggle for civil and human rights, meditating in the modern age on the distance traveled since the days of Jim Crow and segregation. Rooted in Lewis' personal story, it also reflects on the highs and lows of the broader civil rights movement
Keywords: Lewis, John -- 1940- -- Comic books, strips, etc; United States -- Congress -- House -- Biography -- Comic books, strips, etc; Student Nonviolent Coordinating Committee (U.S.) -- Biography -- Comic books, strips, etc; Geschichte 1960-1970; Schwarze. USA; Civil rights movements -- United States -- Comic books, strips, etc; African American legislators -- Biography -- Comic books, strips, etc; Civil rights workers -- United States -- Biography -- Comic books, strips, etc; African Americans -- Civil rights -- Comic books, strips, etc; Autobiographical comic books, strips, etc; Graphic novels; Selma to Montgomery Rights March / (1965 / Selma, Ala.) -- Comic books, strips, etc; March on Washington for Jobs and Freedom / (1963 / Washington, D.C.) -- Comic books, strips, etc; Nonfiction comic books, strips, etc; Bürgerrechtsbewegung; Schwarze; USA; Biografie; Comic